Unveiling the genetic potential and diversity of rice landraces for grain Fe content - Deepika, konne; Shanmugam, Aravindan; Manimaran, Rangarajan; Pushpa, Raman; Bama, Kaliappan Sathiya; Umamageswari, Chellappan; Ramalingam , Suresh (Plant Science Today, 2025)
Addressing micronutrient deficiency is increasingly recognized as a critical aspect of food and nutrition security in developing nations. Leveraging diverse genetic resources offers a promising avenue for identifying and enhancing micronutrient-rich genotypes through breeding strategies, thus providing sustainable solutions to this pressing challenge. The study aimed to identify rice genotypes with high Fe content and to study the extent of genetic divergence based on morphological and grain quality traits in a set of 50 native rice landraces over 2 different locations. A wide range of variation for grain Fe content was observed among the studied genotypes, which varied from 9.28–14.45 mg kg-1 and 1.88–4.87 mg kg-1 in brown and polished rice respectively. Results showed that the genotypes Jaya, Kalanamak, Kottara Samba, Gandakasala and Gopalbhog recorded high grain Fe content before polishing whereas Kottara Samba, Kalapathi Black, Jyothi, Chinnar and Kalanamak were found to have high Fe content after polishing. Interestingly, landraces possessing red seed coat color and medium slender grain group were identified to possess high grain Fe content. This was further substantiated by the correlation study where kernel breadth recorded a negative association with Fe content after polishing. Clustering resulted in 5 groups where the high Fe content possessing genotypes were grouped into clusters 2 and 4. Thus, these genotypes could be utilized as donors in further bio-fortification breeding programs.